Measurement of poverty, deprivation, and economic mobility - Garner, Thesia Isedora; Short, Kathleen (Emerald, 2015)
The papers in Measurement of Poverty, Deprivation, and Economic Mobility represent the most current research on poverty, deprivation, and income mobility. They illustrate the multidimensionality of poverty that is difficult to capture in any one measure. The volume presents state-of-the-art research that is relevant to poverty academics globally. The papers use a variety of methods that measure the persistence of poverty over time and cover numerous countries and circumstances. A selection of papers focus on single countries while others include comparisons of countries. The volume begins with a set of papers that examine particular groups that are most vulnerable to poverty and deprivation in a variety of places. These include measuring the persistence of poverty of immigrant children in Scandinavian countries. Finally the volume concludes with papers that analyze the relationships of two or more measures together to further elucidate what we know if we have only one measure of poverty.
Keywords: Poverty.; elektronické knihy; electronic books